Registration of 'CP 09‐1385' sugarcane. Issue 3 (10th June 2020) - Coto Arbelo, O.; Sandhu, H.S.; Zhao, D.; Gordon, V.; Comstock, J.C.; Sood, S.G.; McCorkle, K.; Davidson, W.; Baltazar, M.; McCord, P.; Singh, M.P.
Abstract: 'CP 09‐1385' (Reg. no. CV‐194; PI 691535) sugarcane, a complex hybrid of Saccharum spp., was developed through cooperative research conducted by the USDA–ARS, the University of Florida, and the Florida Sugar Cane League. It was selected from a biparental cross made at the USDA–ARS Sugarcane Field Station in Canal Point, FL, in December 2006 using the cultivars 'CP 01‐2459' as the female parent and 'CP 00‐2188' as the male parent. CP 09‐1385 was superior to the check cultivars 'CL 88‐4730', 'CP 89‐2143', and 'CP 78‐1628' on sand soils on the basis of cane and sucrose yields, and economic index (i.e., overall profitability). On muck soils, CP 09‐1385 showed superior cane and sucrose yields, and economic index compared with checks CP 78‐1628, CP 89‐2143, and 'CP 00‐1101'. CP 09‐1385 is resistant to brown rust and showed resistance to Sugarcane mosaic virus under artificial inoculation. It is moderately resistant to orange rust, smut, and Sugarcane yellow leaf virus . This new cultivar is moderately susceptible to leaf scald on muck soils but moderately resistant on sand soils. CP 09‐1385 is moderately susceptible to ratoon stunting disease. These susceptibility levels are within an acceptable range for commercial production. Last, CP 09‐1385 demonstrates moderate to low tolerance to freezing conditions. This cultivar was released in June 2016 to be commercially cultivated in Florida on muck and sand lands.